Craniometric Analysis of European Rabbit (Oryctolagus Cuniculus) Breeds to Trace out Intraspecific and Inter Gender Morphometric Variations - Muhammad Rizwan; Rana Manzoor Ahmad; Abdul Majid Khan; Misbah Khalid; Muhammad Wajid (Journal of Bioresource Management, 2021)
The family Liproidae expresses the significant variation of morphometric features at species level. In already available literature on the European rabbit (Oryctolagus cuniculus) the idea is proposed that there can be variation in the morphometric character of different breeds of Oryctolagus cuniculus but there are negligible scientific research base evidences for it. So in this study interbreed craniometric comparison of the European rabbit is carried out to trace out their intergender and intraspecific morphometric variations. The study material consists of 32 sexually mature rabbits belong to two breeds of European rabbit that are New Zealand rabbit (eight males and eight females) and American Dutch rabbit (eight males and eight females) collected from different districts of the Punjab, Pakistan. There were 29 different measurements taken from the skull and mandible of both breeds by using digital and manual verniar calipers. The results of this study have revealed that there is significant interbreed variation in the nasal length measurement of the New Zealand and American Dutch rabbit. This significant interbreed difference in nasal length is observed in both female as well as male rabbits (p=0.0059 and 0.0069 respectively). The current study also depicts that inter gender craniometric variations exist in the New Zealand as well as American Dutch rabbit. The standard deviation of the foramen magnum index of the both included breeds is comparatively higher than all the other included morphometric features. This study provides the baseline data on interbreed craniometric variations in the Oryctolagus cuniculus.